Cerita Pantun Sri Sadana atau Sulanjana Analisis Struktur dan Semiotik (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
This study aims to examine structur of Sri Sadana Sulanjana based on model analysis develoved by Vladimir Propp and Semiotik structure. The principal issues examined in this study include character functions, schemes and pattern of stories, function distributions among characters, and the elements semiotic. The mothod used qualitative descriptive method with classification techniques through literature. The result of the analysis proves that Sri Sadana or Sulanjana hast thirty eight character functions who distributed into seven circles of actions. Thirty eight character functions mentioned found in ten episodes and the semiotic element refers to the symbols in the story content. Keywords: poetry story; Sri Sadana or Sulanjana; structure; semiotics